The Effects of Amphetamine and Methamphetamine on the Release of Norepinephrine, Dopamine and Acetylcholine From the Brainstem Reticular Formation - Ferrucci, Michela; Limanaqi, Fiona; Ryskalin, Larisa; Biagioni, Francesca; Busceti, Carla L.; Fornai, Francesco (Frontiers in Neuroanatomy, 2019)
Amphetamine (AMPH) and methamphetamine (METH) are widely abused psychostimulants, which produce a variety of psychomotor, autonomic and neurotoxic effects. The behavioral and neurotoxic effects of both compounds (from now on defined as AMPHs) stem from a fair molecular and anatomical specificity for catecholamine-containing neurons, which are placed in the brainstem reticular formation (RF). In fact, the structural cross-affinity joined with the presence of shared molecular targets between AMPHs and catecholamine provides the basis for a quite selective recruitment of brainstem catecholamine neurons following AMPHs administration. A great amount of investigations, commentary manuscripts and books reported a pivotal role of mesencephalic dopamine (DA)-containing neurons in producing behavioral and neurotoxic effects of AMPHs. Instead, the present review article focuses on catecholamine reticular neurons of the low brainstem. In fact, these nuclei add on DA mesencephalic cells to mediate the effects of AMPHs. Among these, we also include two pontine cholinergic nuclei. Finally, we discuss the conundrum of a mixed neuronal population, which extends from the pons to the periaqueductal gray (PAG). In this way, a number of reticular nuclei beyond classic DA mesencephalic cells are considered to extend the scenario underlying the neurobiology of AMPHs abuse. The mechanistic approach followed here to describe the action of AMPHs within the RF is rooted on the fine anatomy of this region of the brainstem. This is exemplified by a few medullary catecholamine neurons, which play a pivotal role compared with the bulk of peripheral sympathetic neurons in sustaining most of the cardiovascular effects induced by AMPHs.